A new tribal classification of Crassulaceae subfam. Cotyledonoideae: separating Kalanchoe from Adromischus, Cotyledon, and Tylecodon - Smith, Gideon F.; Monro, Anna M. (Phytotaxa, 2025)
In 2024 finality was reached regarding Crassulaceae subfam. Cotyledonoideae being the subfamily name that must be used, instead of Crassulaceae subfam. Kalanchooideae, for a group of four predominantly, but not exclusively, southern African genera, i.e., Adromischus, Cotyledon, Kalanchoe, and Tylecodon. A conclusion having been reached on this nomenclatural matter facilitates a reassessment of the infrasubfamilial classification of Crassulaceae subfam. Cotyledonoideae as it was amended in 2024. The four genera are here formally split across two tribes, i.e., the pentamerous-flowered, deciduous or evergreen Crassulaceae [subfam. Cotyledonoideae] tr. Cotyledoneae (Adromischus, Cotyledon, and Tylecodon) and the tetramerous-flowered, evergreen Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae (Kalanchoe). These two tribal names were validly published 196 and 92 years ago, respectively. The circumscriptions of both tribes, as originally conceived, are substantially amended.